Consumption of fruit in street posts from eleven iberoamerican countries. Multicentric study - Duran Aguero, SD (2020)
Introduction: The street food intake is a very common practice in working people. There is a great supply of street food; fruits are always part of this offer and can be found in different presentations Objetive: To analyze the frequency of fruit consumption in public roads in Latin America. Material and Methods: A cross-sectional study was carried out using a questionnaire of 15 questions in Google Docs format, which was validated by Delphi method and applied in 11 countries: Argentina, Brazil, Chile, Colombia, Costa Rica, Guatemala, Panama, Paraguay, Peru, Portugal and Uruguay. Results: It was surveyed 8885 people, over 50% consume food on public roads; among the most consuming countries, it is highlighted Colombia (78%) and Guatemala (76%), followed by Peru (66%). With respect to fruit consumption on public roads, it is observed that there is higher consumption in Portugal (61%), followed by Colombia (55%) and Guatemala (51%), and the countries with less consumption are Argentina (26%) and Uruguay (20%). Fruit consumption in the street is the same in both sexes in the most countries. On the other hand, in Portugal, Colombia, Argentina, Costa Rica and Chile, the highest consumption correspond to people with higher education (university or post-graduate) (p<0.05). Conclusion: Street food consumption is high in all countries, including consumption of fruits. This can be transformed into an opportunity to encourage their consumption, but street posts must be adjusted to the necessary requirements to offer safe food.